Homogeneous Cytochrome 579 Is an Octamer That Reacts Too Slowly With Soluble Iron to Be the Initial Iron Oxidase in the Respiratory Chain of Leptospirillum ferriphilum - Blake, Robert C.; Shively, John E.; Timkovich, Russell; White, Richard Allen (Frontiers in Microbiology, 2021)
The exact role that cytochrome 579 plays in the aerobic iron respiratory chain of Leptospirillum ferriphilum is unclear. This paper presents genomic, structural and kinetic data on the cytochrome 579 purified from cell-free extracts of L. ferriphilum cultured on soluble iron. Electrospray mass spectrometry of electrophoretically homogeneous cytochrome 579 yielded two principal peaks at 16,015 and 16,141 Daltons. N-terminal amino acid sequencing of the purified protein yielded data that were used to determine the following: there are seven homologs of cytochrome 579; each homolog possesses the CXXCH heme-binding motif found in c-type cytochromes; each of the seven sequenced strains of L. ferriphilum expresses only two of the seven homologs of the cytochrome; and each homolog contains an N-terminal signal peptide that directs the mature protein to an extra-cytoplasmic location. Static light scattering and macroion mobility measurements on native cytochrome 579 yielded masses of 125 and 135 kDaltons, respectively. The reduced alkaline pyridine hemochromogen spectrum of the purified cytochrome had an alpha absorbance maximum at 567 nm, a property not exhibited by any known heme group. The iron-dependent reduction and oxidation of the octameric cytochrome exhibited positively cooperative kinetic behavior with apparent Hill coefficients of 5.0 and 3.7, respectively, when the purified protein was mixed with mM concentrations of soluble iron. Consequently, the extrapolated rates of reduction at sub-mM iron concentrations were far too slow for cytochrome 579 to be the initial iron oxidase in the aerobic respiratory chain of L. ferriphilum. Rather, these observations support the hypothesis that the acid-stable cytochrome 579 is a periplasmic conduit of electrons from initial iron oxidation in the outer membrane of this Gram-negative bacterium to a terminal oxidase in the plasma membrane.